Day 1 Mon, April 25, 2022 2022
DOI: 10.2118/209467-ms
|View full text |Cite
|
Sign up to set email alerts
|

First Nanoparticle-Based EOR Nano-EOR Project in Japan: Laboratory Experiments for a Field Pilot Test

Abstract: "Nanoparticle-based enhanced oil recovery (Nano-EOR)" is an improved waterflooding assisted by nanoparticles dispersed in the injection water. Many laboratory studies have revealed the effectiveness of Nano-EOR. An evaluation of the EOR effect is one of the most critical items to be investigated. However, risk assessments and mitigation plans are as essential as investigation of its effectiveness for field applications. This study examined the items to be concerned for applying Nano-EOR to the Sarukawa oil fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Afekare et al 22 also showed how aqueous dispersions of hydrophilic nanosilica may have a significant effect on the reduction (>70%) of the rock–oil adhesion force and work of adhesion (>95%), which leads to nanoscale wettability improvement and a potential increase in the recovery factor. Kaito et al 23 utilized a 0.5 wt % surface-modified nanosilica dispersion (SND), which contains 18% colloidal silica nanoparticles and some chemicals to enhance the stability of nanoparticles in synthetic brine, to show that nanoparticles increased oil recovery by 14 points in most core-flooding experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Afekare et al 22 also showed how aqueous dispersions of hydrophilic nanosilica may have a significant effect on the reduction (>70%) of the rock–oil adhesion force and work of adhesion (>95%), which leads to nanoscale wettability improvement and a potential increase in the recovery factor. Kaito et al 23 utilized a 0.5 wt % surface-modified nanosilica dispersion (SND), which contains 18% colloidal silica nanoparticles and some chemicals to enhance the stability of nanoparticles in synthetic brine, to show that nanoparticles increased oil recovery by 14 points in most core-flooding experiments.…”
Section: Introductionmentioning
confidence: 99%